2012
DOI: 10.1080/07418825.2012.723030
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Pursuit: A Conceptual and Empirical Comparison of Cyberstalking and Stalking Victimization Among a National Sample

Abstract: Cyberstalking is a relatively understudied area in criminology, with no consensus among scholars as to whether it represents a modified form of stalking or whether it is an entirely new and emerging criminal phenomenon. Using data from the 2006 Supplemental Victimization Survey to the National Crime Victimization Survey, this study compares stalking and cyberstalking victims across several dimensions, including situational features of their experiences and self-protective behaviors. Results indicate that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 65 publications
4
127
1
4
Order By: Relevance
“…To be classified as a stalking victim, respondents had to report experiencing two or more stalking behaviors as there was not a measure of ''repeated'' behaviors in the survey instrument. These items are commonly used in the current stalking victimization literature [see Fox et al (2016); Nobles et al (2014)] and provide a widely accepted basis for estimating stalking victimization in the sample.…”
Section: Victimization Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…To be classified as a stalking victim, respondents had to report experiencing two or more stalking behaviors as there was not a measure of ''repeated'' behaviors in the survey instrument. These items are commonly used in the current stalking victimization literature [see Fox et al (2016); Nobles et al (2014)] and provide a widely accepted basis for estimating stalking victimization in the sample.…”
Section: Victimization Variablesmentioning
confidence: 99%
“…A recent German study of social networking platforms reported that almost half of users experienced online harassment, resulting in approximately half of these cases escalating to cyberstalking, with females being significantly more likely to be victims (Dreßing et al 2014). In many instances, cyberstalking behaviors occur concurrently with traditional offline stalking behaviors (Dreßing et al 2014;Nobles et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Using data from the 2006 NCVS to compare traditional stalking and cyberstalking victims, Nobles, Reyns, Fox, and Fisher (2014) reported that individuals stalked via electronic means employed more self-protective behaviors, such as changing usual activities and changing email addresses, in comparison with traditional stalking victims. The authors offered an explanation for their findings couched in the dynamics of online interaction as they suggested that communication via electronic means is just as personal as, or more personal than, face-to-face communication and therefore cyberstalking may elicit a personal violation, which consequently elicits more diverse self-protective behaviors.…”
mentioning
confidence: 99%
“…Yet, important questions remain surrounding this relatively new form of victimization. As is the case with other related forms of cybercrime victimization, such as cyberstalking or online harassment, it is not clear whether cyberbullying is a unique behavior, separate and distinct from its physical counterpart or simply an extension of traditional bullying carried out in cyberspace [32].…”
Section: Cyberbullyingmentioning
confidence: 99%